A Safe Anti-A2 Titer for a Successful A2 Incompatible Kidney Transplantation: A Single-center Experience and Review of the Literature. Issue 2 (26th January 2021) - Azzi, Yorg; Nair, Gayatri; Loarte-Campos, Pablo; Ajaimy, Maria; Graham, Jay; Liriano-Ward, Luz; Pynadath, Cindy; Uehlinger, Joan; Parides, Michael; Campbell, Alesa; Colovai, Adriana; Alani, Omar; et al.
Abstract : Background: Kidney allocation system allows blood type B candidates accept kidneys from A2/A2B donors. There is no mandate by UNOS on which the anti-A2 level is acceptable. We aimed to investigate the safety of kidney transplant in blood group B patients with anti-A2 titers ≤16. Methods: We performed 41 A2-incompatible kidney transplants in blood group B recipients between May 2015 and September 2019. Clinical outcomes were compared with a control group of 75 blood group B recipients who received blood group compatible kidney transplantation at the same period. Results: Of the 41 recipients, 85% were male, 48% African American, with a median age of 53 (20–73) y. Thirty-eight (93%) were deceased-donor and 3 (7%) were living-donor kidney transplant recipients. Pretransplant anti-A2 IgG titers were 2 in 16, 4 in 9, 8 in 6, and 16 in 5 and too weak to titer in 5 recipients. Eight patients had pretransplant donor-specific antibodies. During a median follow-up of 32.6 mo (6–57.3) patient and graft survival were 100% and 92% in the A2-incompatible kidney transplant group, and 91% and 92% in the blood group compatible group, respectively. Twelve A2-incompatible recipients underwent a 21 clinically indicated kidney biopsies at a median 28 d (6–390) after transplantation. None of the patients developed acute antibody-mediated rejection and 2 patients (5%) had acute T-cell–mediated rejection. Interestingly, peritubular capillary C4d positivity was seen in 7 biopsies which did not have any findings of acute rejection or microvascular inflammation but not in any of the rejection-free biopsies in the control group. C4d positivity was persistent in 5 of those patients who had follow-up biopsies. Conclusions: A2-incompatible transplantation is safe in patients with anti-A2 titers ≤16 with excellent short-term kidney allograft outcomes. C4d positivity is frequent in allograft biopsies without acute rejection.